PERANCANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI PADA MATERI PENJUMLAHAN DAN PENGURANGAN MATA PELAJARAN MATEMATIKA PADA KELAS 1 TAHUN 2025 DI SD NEGERI JOGLO SURAKARTA - Wahyu Aditya Nugraha; Sri Handayani; Daryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to 1) design an Android-based learning media for the mathematics subject of addition and subtraction for grade I of SD Negeri Joglo Surakarta using the Adobe Flash CS 3 application; 2) to assess the feasibility level of the Android-based learning media design as a mathematics learning medium for addition and subtraction for grade I of SD Negeri Joglo Surakarta. This study uses the Research and Development method with the ADDIE development model. Data collection uses observation, interview, questionnaire, and documentation techniques. The testing system uses Blackbox Testing and feasibility validation by experts and student responses to provide responses regarding the feasibility of the learning media, then the product feasibility validation is analyzed and converted using a Likert Scale. The results of this study indicate that the designed learning media obtains very feasible criteria, according to media expert validation it has a feasibility level of 94% with very feasible criteria, according to material expert validation it has a feasibility level of 91% with very feasible criteria, according to teacher expert validation (educators) it has a feasibility level of 93% with very feasible criteria, and the feasibility assessment by students gets a percentage of 95% with very feasible criteria.